Industrial policy formulation in Thailand, Malaysia and Japan : (Social Labour, 2006)
The book would like to share the studying with broader community of policy makers and researchers in Vietnam about the finding the industrial policies, and how policies were designed, implemented, reviewed, and how the government and the business community talked together in the experienced neighbourhood countries e.g. Thailand, Malaysia and Japan.